The effectiveness of promotional strategy: a case study of TM Net Sdn. Bhd. Kota Bharu / Nor Izzati A. Malek @ Abdul Malek - A. Malek @ Abdul Malek, Nor Izzati (2005)
The purpose of this study is to identify the effectiveness of promotional strategy engaged by TM Net Sdn. Bhd. Kota Bharu. This study is conducted in order to measure whether the promotional strategies done by the company is effective or not. The study also allows us to determine which promotional tool is the most effective and the less effective based on the company's sales achievement. The study mostly uses secondary data as it is one of the important sources in complete the research. The data come from the company's annual sales reports and other reliable literature. In analyzing the data, percentage calculation, gap scale and ranking examination were employed. The study discovered and identified that the effective promotional strategies engaged by the company are personal selling and exhibition meanwhile, the sales promotion is ineffective. The study also measured that the personal selling campaign is on the first rank of level of effectiveness, followed by exhibition as the second rank and the last rank is sales promotion campaign.